Comparison of the incidence, mechanisms, and risk factors of anterior cruciate ligament injury during rotational knee trauma in skiers and snowboarders. A Perspective of Recent Literature. - Brzoza, Joanna; Łukasz Dylewicz,; Kinga Bylica,; Jakub Rudzki,; Wojciech Warmuz,; Ewa Wystalska,; Kacper Solarz,; Natalia Czołpińska,; Zuzanna Kata,; Jakub Andrzejewicz, (Quality in Sport, 2026)
Knee injuries are among the most common and clinically significant injuries in winter sports, particularly in alpine skiing and snowboarding. Differences in sport-specific biomechanics and equipment constraints are thought to influence both injury incidence and patterns. The aim of this study is to compare the incidence, mechanisms, and risk factors of rotational knee injuries in individuals participating in skiing and snowboarding. Understanding the differences in injury mechanisms and identifying associated risk factors are essential for the development of effective prevention strategies and optimization of treatment. A comparative analysis of rotational knee injuries in skiers and snowboarders enables a better understanding of the specific characteristics of these disciplines and may contribute to reducing the incidence of such injuries in the future.